Fungal Architectures - Adamatzky, Andrew; Wösten, Han; Ayres, Phil (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint presents groundbreaking discoveries, practical techniques, and rigorous analyses related to the cultivation, preparation, and exploitation of mycelium composites. The papers cover a wide range of topics, including functional modifications of mycelium with inorganic particles, modifying and assessing the mechanical properties of mycelium composites, strategies for improving the flexural behaviour of composites, beehives from fungal materials, bio-welding and reinforcement of composites, bioreactors for fungal production, co-production of composites by fungi and bacteria, growing large-scale mycelium structures, sound absorption by composites, and the geometrical parameterisation of fungi. This informative compendium of techniques, methods, and insights on growing fungal material appeals to readers from all walks of life, from high school pupils to university professors, from mathematicians, computer scientists, and engineers to chemists, from craft practitioners to industrial producers of fungal materials, and from biologists to architects and artists.